538 The Value of Near-Infrared Spectroscopy (Nirs) in Perinatal Asphyxia-A Case Report. (October 2012) - Norooz, F; Urlesberger, B; Klebermasz-Schrehof, K; Czaba, C; Obwegeser, E; Giordano, V; Berger, A; Weninger, M; Olischar, M
Abstract : Background: Perinatal asphyxia remains a challenging entity. NIRS offers a method to continuously monitor cerebral oxygen saturation. Aim: To obtain insight into haemodynamic changes during hypothermia and rewarming in perinatal asphyxia using NIRS. Methods: We report of an asphyxiated patient (37+6 weeks', Apgar 6 and 8 at 1 and 5 minutes, first arterial blood gas pH of 6.67, base deficit –25). NIRS was started during the first hour of life and continued for a total recording time of 125 hours. Simultaneously, we measured brain function using amplitude-integrated electroencephalography (aEEG). On day 7 magnetic resonance imaging (MRI) has been performed. After discharge, the patient was reassessed neurologically. Results: The initial cerebral rSO2 was 65%. When cooling was started FTOE was 0.28. At 33.5°C FTOE had decreased to 0.20, cerebral rSO2 increased to 70%. After rewarming cerebral rSO2 was 85%, and FTOE 0.11. Initially, aEEG showed a mixed burst-suppression and discontinuous pattern which improved to a discontinuous pattern only during the first 12 hours. After rewarming aEEG normalized and showed developing sleep-wake cycles. MRI did not show any signs of hypoxic damage. After discharge the patient presented neurodevelopmentally normal. Conclusion: After having cooled down the patient, both NIRS and aEEG showed an improvement (increase of rSO2, decrease of FTOE, loss of burst-supression in aEEG). aEEG displays cerebral function, cerebral NIRS expands information to cerebral oxygen supply and extraction. MRI and neurodevelopmental assessment proved the observed aEEG and NIRS data.